2017
DOI: 10.1002/2016jb013874
|View full text |Cite
|
Sign up to set email alerts
|

Synchrotron tomographic quantification of strain and fracture during simulated thermal maturation of an organic‐rich shale, UK Kimmeridge Clay

Abstract: Analyzing the development of fracture networks in shale is important to understand both hydrocarbon migration pathways within and from source rocks and the effectiveness of hydraulic stimulation upon shale reservoirs. Here we use time‐resolved synchrotron X‐ray tomography to quantify in four dimensions (3‐D plus time) the development of fractures during the accelerated maturation of an organic‐rich mudstone (the UK Kimmeridge Clay), with the aim of determining the nature and timing of crack initiation. Electro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
19
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 42 publications
(55 reference statements)
4
19
0
Order By: Relevance
“…4 ). The geometry of pores is expected to affect significantly the propagation of induced fractures and porous flow behaviours 10 , 35 , 36 , but it has not been possible to evaluate these influences in many other models. The pore geometry and networking demonstrated here has the potential to provide higher accuracy and applicability to petrophysical modelling than an approach based solely on pore-throat sizes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…4 ). The geometry of pores is expected to affect significantly the propagation of induced fractures and porous flow behaviours 10 , 35 , 36 , but it has not been possible to evaluate these influences in many other models. The pore geometry and networking demonstrated here has the potential to provide higher accuracy and applicability to petrophysical modelling than an approach based solely on pore-throat sizes.…”
Section: Discussionmentioning
confidence: 99%
“…The key properties of shales that underpin commercial viability and minimize environmental impact, such as permeability, storativity, elastic properties and electrical conductivity, are directly related to pore-size distribution, pore geometry and the connectivity of the pore network 8 , 9 . For example, the location of nano-pores associated with organic matter or phyllosilicate minerals are pivotal not only for understanding pore generation and evolution during maturation and fracturing 10 , but also in controlling and influencing gas transport and storage 11 .…”
Section: Introductionmentioning
confidence: 99%
“…Cracking induced by accelerated (i.e., ex-situ) desiccation of a cement paste containing glass beads was quantified via DVC [101]. Similarly, accelerated maturation of Kimmeridge clay was monitored in-situ up to 380°C [63] with 2-min acquisitions of 1800 radiographs. Sintering of copper was monitored in-situ at 1050°C.…”
Section: Introductionmentioning
confidence: 99%
“…Microstructural heterogeneities such as variations of grain size, shape, mineralogy, elasticity, anisotropy and stiffness, together with preexisting defects can create local stress concentrations. Such stress concentrations influence the initiation and behavior of fractures in shales, such as hydraulic fractures (Keneti and Wong 2010), mechanical fractures (Van de DRAFT Feb 2018 -5 Steen et al, 2003) and desiccation fractures (Hedan et al, 2012;Fauchille et al, 2016;Figueroa Pilz et al, 2017) in response to the local stress field. In a general sense, Sone and Zoback (2013) and Amann et al, (2014) have shown how significantly the microstructure can impact upon the mechanical properties of shale.…”
Section: Introductionmentioning
confidence: 99%